DEFINING TOLERANCE MEANING OF THE RELIGIOUS CONTEXT AT PALAS VILLAGE, RUMBAI DISTRICT, PEKANBARU CITY RIAU - M Hidayat; Eris Wandi; Nurhasanah Bakhtiar (IAIN Salatiga, 2019)
This research has been conducted at Palas Village, Rumbai District, Pekanbaru City. The aim of the study is to demonstrate the values of religious tolerance in the context of Palas village in Pekanbaru. This study entitled “Understanding Tolerance in the Religious Context”. The study conducted through survey where the researchers went to the field and conducted interviews. The study used method of sampling by purposive sampling. The researchers choose samples with several considerations of data instrument such as observation, interviews, and documentation. The findings of the study showed that the attitude of mutual respect plays key role in maintaining tolerance in religion and keeping the unity in society. This tolerance will also avoid the conflicts in the community. Lastly, the community is encouraged to maintain and realise between rights and obligations among others.